Political sarcasm on tiktok account @podcastkeselaje - Abdullah, Alwi; Adek, Muhammad; Putra, It Fernando (Universitas Ahmad Dahlan, 2022)
Recently, there has been apprehension in the society about expressing ideas, particularly on political concerns. As a result, public figures such as comedians tend to use sarcasm as their primary weapon in exposing political leaders' weakness, incompetence, or corrupt behavior, as well as government officials' actions. The goal of this research is to look at the form, meaning, and function of sarcasm on the TikTok account @Podcastkeseaje. All of the utterances said by the narrator or speakers in the video recording from the TikTok account @podcastkeselaje are used as data sources in this study. Indirect observation was used to obtain data, which was then followed by recording and note-taking techniques. The data were examined using Camp's (2012) theory for the form of sarcasm, Chaer's (2009) theory for the meaning of sarcasm, and Chaer's (2009) theory for the meaning of sarcasm.